2006
DOI: 10.1371/journal.pone.0000054
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Side of EGFP: Defective Polyubiquitination

Abstract: Enhanced Green Fluorescent Protein (EGFP) is the most commonly used live cell reporter despite a number of conflicting reports that it can affect cell physiology. Thus far, the precise mechanism of GFP-associated defects remained unclear. Here we demonstrate that EGFP and EGFP fusion proteins inhibit polyubiquitination, a posttranslational modification that controls a wide variety of cellular processes, like activation of kinase signalling or protein degradation by the proteasome. As a consequence, the NF-κB a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
97
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(98 citation statements)
references
References 28 publications
(36 reference statements)
1
97
0
Order By: Relevance
“…This vector Ubiquilin-1 Is a Molecular Chaperone has been described elsewhere, and this particular GFP variant has been shown to have no effect on proteasomal degradation (35). PCR primers were 5Ј-TTC AAG CTT CCA TGC TGC CCG GTT TGG CAC TG-3Ј and 5Ј-TCC CCG CGG GTT CTG CAT CTG CTC AAA GAA CTT GTA G-3Ј.…”
Section: Methodsmentioning
confidence: 99%
“…This vector Ubiquilin-1 Is a Molecular Chaperone has been described elsewhere, and this particular GFP variant has been shown to have no effect on proteasomal degradation (35). PCR primers were 5Ј-TTC AAG CTT CCA TGC TGC CCG GTT TGG CAC TG-3Ј and 5Ј-TCC CCG CGG GTT CTG CAT CTG CTC AAA GAA CTT GTA G-3Ј.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the fusions to MotB induce a novel BFM dynamic that involves an asymmetry in the speeds attained in opposing rotational directions, depending on the motor's bias. These effects of the fluorescent fusion proteins on the BFM could be partially restored by a rigid linker (EAAAK) 3 inserted at the fusion point. Together, these findings reveal how a fluorescent protein fusion that does not abolish function completely can modulate biologically relevant dynamics of a protein complex and even induce new behavior, all of which can be partially relieved by the incorporation of a linker.…”
Section: Discussionmentioning
confidence: 99%
“…In order to choose the best linker, the population motility was measured for Dendra2 stators joined to four different linkers of the following sequences (see Fig. 5D): (GGGGS), (EAAAK), (GGGGS) 3 , and (EAAAK) 3 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, green fluorescent protein (GFP) is considered nontoxic both in in vitro and in vivo systems. However, there are some reports showing side effects of GFP in in vitro and in vivo studies, but the details of molecular mechanism of these interactions still remain unclear (Agbulut et al, 2006(Agbulut et al, , 2007Baens et al, 2006;Huang et al, 2000;Liu et al, 1999). Recently, it has been shown that Ku80 attenuates cytotoxicity induced by green fluorescent protein transduction independently of non-homologous end joining (Koike et al, 2013).…”
Section: Introductionmentioning
confidence: 99%